2017
DOI: 10.1007/s00704-017-2122-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance and evaluation of a coupled prognostic model TAPM over a mountainous complex terrain industrial area

Abstract: Atmospheric modeling is considered an important tool with several applications such as prediction of air pollution levels, air quality management, and environmental impact assessment studies. Therefore, evaluation studies must be continuously made, in order to improve the accuracy and the approaches of the air quality models. In the present work, an attempt is made to examine the air pollution model (TAPM) efficiency in simulating the surface meteorology, as well as the SO 2 concentrations in a mountainous com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…TAPM also simulated well the surface wind speed in the study area, with the mean values of both predicted and observed wind speed were approximate 2 m/s during the study period. However, it slightly overestimated the wind speed comparing with observed value and with 0.4 and 0.7 m/s difference in February and June, respectively, which were the same ranges as those in Matthaios's study 23 . Figure 3 and Table 3 present the performance of SO 2 , NO 2 , and O 3 from 12 th to 17 th June 172017.…”
Section: Results and Discusionsupporting
confidence: 78%
See 1 more Smart Citation
“…TAPM also simulated well the surface wind speed in the study area, with the mean values of both predicted and observed wind speed were approximate 2 m/s during the study period. However, it slightly overestimated the wind speed comparing with observed value and with 0.4 and 0.7 m/s difference in February and June, respectively, which were the same ranges as those in Matthaios's study 23 . Figure 3 and Table 3 present the performance of SO 2 , NO 2 , and O 3 from 12 th to 17 th June 172017.…”
Section: Results and Discusionsupporting
confidence: 78%
“…However, TAPM slightly underestimated the temperatures during the dry season but a little overestimated during the rainy season. This result also agreeded with the findings in Matthaios's study in 2018 about the evaluation of TAPMP model over a mountainous complex terrain industrial area 23 .…”
Section: Loading Capactiessupporting
confidence: 91%
“…During the summer months these temperature values are 23.7, 29.4 and 17.9 °C, respectively. For the same period, the prevailing winds in the industrial basin are weak to mediocre and mainly blow with NW/SE direction ( Figure 2) due to channeling of the synoptic wind (Matthaios et al, 2018). Strong ground base nocturnal inversions are observed in the basin where the main industrial activity take place during the whole period of the year.…”
Section: Study Areamentioning
confidence: 92%
“…TAPM is an operational, threedimensional (3D) terrain following sigma-coordinate, coupled prognostic meteorological and pollutant dispersion model, that uses the fundamental equations of atmospheric flow, thermodynamics, moisture conservation, turbulence, and dispersion (Hurley et al, 2001;Hurley et al, 2003a;Hurley et al, 2003b). The model was configured, ran and validated in the area of interest by Triantafyllou et al (2011); Aidoui et al (2015) and Matthaios et al (2017). Based on the model results tailored to this study, out of the eight locations studied, the two areas -receptors of natural P. nigra populations, associated with the extreme concentrations (maximum and minimum), were selected, following a methodology adapted from Rajput and Agrawal (2005).…”
Section: Population Selection and Samplingmentioning
confidence: 99%